Critical Geography from Within: Embodied Standpoints, Visibilisation and Reparative Praxis - Behzadi, Negar Elodie (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2026)
This paper reflects on what it means to do critical geography today by tracing its complex history and situating it within my own positionality as a feminist political geographer inspired by post/de/anti-colonial perspectives. While critical geography is often located in the radical movements of the 1960s-1970s in North America and Europe, these accounts overlook wider and earlier histories of critique, and the contributions of non-white, non-male, and non-Anglophone thinkers. I argue that critical geography has always been plural, shaped by feminist, anti-racist, postcolonial, and Global South perspectives that have since become central to the discipline. Writing from a standpoint shaped by my own history of migration, displacement, and simultaneous privilege within academia, I emphasise that our positions influence the forms of critique we produce. I describe this approach as the production of knowledge from within out: a way of engaging with the world that acknowledges how embodied, emotional, and experiential ways of knowing can generate critical insight. From this perspective, I outline my two key commitments in doing critical geography today based on my own work. The first is a Politics of Visibilisation – making visible the systemic, intimate, and embodied violences of extraction, displacement, and exhaustion. The second is a Reparative Praxis, which asks how we might move beyond critique toward responsibility, creativity, and care. Drawing on feminist and art-based methodologies, I suggest that critical geography can be a reparative and participatory practice, one that not only exposes injustice but also nurtures resilience, connection, and the possibility of repair.